Incidence of sternocutaneous fistulas following open heart surgery in a nationwide cohort. - Steingrímsson, Steinn; Sjögren, Johan; Gudbjartsson, Tomas (Scandinavian Journal of Infectious Diseases, 2013)
To access publisher's full text version of this article. Please click on the hyperlink in Additional Links field. We studied the incidence and characteristics of surgically treated sternocutaneous fistulas in a nationwide cohort of patients undergoing open heart surgery in Iceland. Between 2000 and 2010, sternocutaneous fistulas were treated surgically in 6 out of 2446 patients undergoing open heart surgery (incidence 0.25%, 95% confidence interval 0.11-0.53%). All patients were male, with a mean age of 71 ± 9 y. In addition to antibiotic treatment, debridement of the wound was performed in all cases. Staphylococcus aureus and/or coagulase-negative staphylococci were identified as pathogens in 5 cases and Candida albicans in 1. Chronic infections developed in 3 patients who were treated repeatedly, 1 of them unsuccessfully. In-hospital stay ranged from 0 to 50 days (mean 19 days). Sternocutaneous fistulas are rare, but since they may have a devastating course, increased awareness of this infectious complication of open heart surgery is important.